Investigation of Hybrid Remote Fiber Optic Sensing Solutions for Railway Applications - Boynukalin, Serhat; Paker, Selçuk; Atieh, Ahmad (MDPI AG, 2023)
Fiber optic sensing (FOS) has become a well-known technology in response to the rising demands of the railway transportation field despite the abundance of electronic sensing systems in the market. FOS application boasts an all-in-one solution that is both efficient and versatile. In order to enhance the understanding of the capabilities of FOS, this paper presents a hybrid fiber optic sensing system with an improved sensing ability to facilitate transportation applications for primary or secondary security interfaces. The hybrid sensing scheme incorporates two different sensing systems designed for long-distance applications. The first system employs a coding technique for the transmitted pulses, which provide information on train location through cross-correlation with the reflected pulses from fiber Bragg grating (FBG) sensors located along the railway. The proposed system can accurately predict the train’s location up to a precision of one cm. The second system examines the wavelength drift of the reflected signal from the FBG sensor affected by the train using a tunable optical filter and photodetector. It determines essential parameters such as the train’s location, speed, and direction by measuring the Bragg wavelength shift and its direction. The effect of the train movement and speed on the applied strain on the FBG sensor is calculated in this work and applied to the simulation to determine the train’s location, speed, and direction. A calibration table facilitates the correlation between the train speed and the shift in the FBG center wavelength, which helps ensure accurate results. The hybrid fiber optic sensing system is designed to facilitate railway transportation applications’ sustainability and security.
Keywords: transportation; fiber optic sensing (FOS); railway; transportation; cross-correlation; PN-Coding; FBG; Bragg shifting; FBG; fiber optic sensing (FOS); cross-correlation; railway; TA1501-1820; Applied optics. Photonics; PN-Coding